Application of C4.5 Algorithm in Classification of Personality Types Based on KSPM Personality Theory - Alfian Alfian (JATISI (Jurnal Teknik Informatika dan Sistem Informasi), 2021)
In today's technological developments, all lines of life must have been computerized. Likewise in a system of determining the type of personality type that is able to assist psychologists in completing their duties easily and perfectly. In this study, the system to be built uses an online-based desktop interface. In this study using a decision tree algorithm, where this method is a method that is quite suitable in terms of classification. Based on a study conducted by Florence Littauer that human personality has been classified into four types. The four are included in the protopsychological theory, this theory is divided into four basic personality types, namely choleric, sanguine, phlegmatic, and melancholic (KSPM). There are many ways to determine a person's personality. One of them is to use the decision tree c4.5 algorithm to carry out the process of classifying a person's personality. Decision tree c4.5 algorithm is a classification method that is widely used for classification problems. Decision tree algorithm c4.5 serves to explore data and model a group of data that has not been classified.